Archaeogenomic insights into commensalism and regional variation in pig management in Neolithic northwest Europe - Jolijn A. M. Erven; Valeria Mattiangeli; Merita Dreshaj; Victoria E. Mullin; Conor Rossi; Kevin G. Daly; Iseult Jackson; Mike Parker Pearson; Daniel G. Bradley; Laurent A. F. Frantz; Ole Madsen; Daan Raemaekers; et al. (Proceedings of the National Academy of Sciences, 2025)
The relationship between humans and pigs has changed dramatically since their domestication in southwest Asia and subsequent human-induced introduction into Europe. Introgression between incoming southwest Asian pigs and European boar resulted in the gradual replacement of southwest Asian ancestry in European pigs. However, we currently lack genomic data required to explore the regional trajectories, nature, and extent of contact between European boar and pigs that led to this turnover, and how this process was facilitated by human activity. We addressed this deficit by sequencing four Mesolithic boar and seven Neolithic pig samples from six archaeological sites in the Netherlands and Britain ranging from the Mesolithic (5500 BCE) to Neolithic (2500 BCE). Our data show that despite continuous gene flow with European boar, Neolithic European pigs show varying levels of southwest Asian ancestry. The low and varying southwest Asian ancestry in pigs from the Early Neolithic Dutch settlement Swifterbant indicates a high contribution of wild ancestry. The genetic profile, enriched δ 15 N values, on-site presence, and wide size distribution of Swifterbant Sus scrofa suggest a commensal relationship. Runs of homozygosity (ROH) imply that both closed-breeding and free-ranging management occurred in Neolithic communities, where the former showed an extreme burden of long segments of ROH. We further show selection signatures, associated with coat color and behavior, in Neolithic herds despite recurrent wild gene flow. Altogether, our results show distinct husbandry practices through space and time in Neolithic Europe, with heavy reliance on boar recruitment via the commensal pathway in northwest Europe.